Trypanosoma vivax in and outside cattle blood: Parasitological, molecular, and serological detection, reservoir tissues, histopathological lesions, and vertical transmission evaluation - de Melo-Junior, Rubens Dias; Bastos, Thiago Souza Azeredo; Couto, Luiz Fellipe Monteiro; Cavalcante, Alliny Souza de Assis; Zapa, Dina María Beltrán; de Morais, Igor Maciel Lopes; Heller, Luciana Maffini; Salvador, Vanessa Ferreira; Leal, Luccas Lourenzzo Lima Lins; Franco, Artur de Oliveira; Miguel, Marina Pacheco; Ferreira, Lorena Lopes; et al. (Elsevier, 2024)
This study reports assessment of the sensitivity of diagnostic techniques to detect T. vivax in experimentally infected cattle. Additionally, it describes T. vivax extravascular parasitism during the acute and chronic phases of trypanosomosis and congenital transmission. The T. vivax diagnosis was compared using blood samples collected from the jugular, coccygeal and ear tip veins. For this study, 13 males and two females were infected with ≈ 1 × 106 viable T. vivax trypomastigotes (D0). One animal was kept as a negative control during the entire study. The 13 infected males were euthanized between 14 and 749 days post-infection (DPI). After confirming the cyclicity of both females (9 months of age), they were naturally mated with a bull. One female was euthanized at 840 DPI, and the other at 924 DPI. The two calves, one from each female, were euthanized at six months of age (924 DPI), and the negative control at 924 DPI. During this period, T. vivax in blood was assessed using direct methods (Woo test, cPCR, microscopic examination of fresh wet blood films and parasite quantification - Brener method), and serological methods (IFAT, ELISA, and IA). Tissue samples were collected from the liver, spleen, brain, cerebellum, heart, testicles, epididymis, kidneys, eyeballs, pre-scapular lymph nodes, ear tips, mammary glands, uterus, and ovaries. The protozoan DNA was examined using LAMP. There was no difference in the detection of T. vivax using the Woo test and Brener method among the jugular, coccygeal, and ear tip veins. The sensitivity of the detection methods varied depending on the disease phase. Direct methods (Woo test, Brener method, and cPCR) demonstrated higher sensitivity during the acute phase, while serological methods (IFAT, ELISA, and IA) were more sensitive during the chronic phase. Anti-T. vivax antibodies were detected up to 924 DPI. Tissue evaluation using LAMP demonstrated the presence of T. vivax DNA and associated histopathological changes up to 840 or 924 DPI. Only in mammary glands and ovaries was no DNA detected. The most frequently observed histopathological alteration was lymphohistioplasmocytic inflammatory infiltrate. No transplacental transmission of T. vivax was observed.